ANNUAL PRODUCTION TRENDS IN TENERA HYBRIDS OF OIL PALM IN ANDHRA PRADESH - P. MADHAVI LATHA*, M. TIRUPATI REDDY, B. PRATAP; H.P. MAHESWARAPPA (The Journal of Research ANGRAU, 2020)
Ten oil palm crosses (tenera) were evaluated for 10 harvest years for their growth and yield. Growth of oil palm crosses has not varied significantly among the crosses for palm height and girth. Palm height increment was more than three times from 6th year of harvest to 10th year of harvest, that is 1.00 m to 3.93 m. Annual palm height increment was at the rate of 0.3 to 0.35 m up to seventh harvest year but from eighth to tenth harvest years, palm height increment was at the rate of 0.47 to 0.58 m per year, percent height increment was higher at early harvest years than at later harvest years. Raise and fall in bunch production in every alternate year was the trend up to 9th harvest year. Bunch production and average bunch weight are in inverse relation. Increase in bunch production in a harvest year recorded decrease in average bunch weight of that production year. In the 10th harvest year, bunch production drastically reduced to 6.34 bunches, while average bunch weight in the10th harvest year was high (18.15 kg). The cross NRCOP-4 produced higher number of bunches (13.72) at the sixth harvest year, recording FFB yield of 190.23 kg palm-1 with productivity of 23.39t ha-1.. There was an yield increment by increase in age of palms up to 11 years (8th harvest year). At the 8th harvest year mean per palm yield in the crosses reached to 181 kg recording a productivity of 22.26 t ha-1. Yield increment was four times in the first four harvest years (17.97 to 86.74 kg palm-1) where this period of production can be considered as yield incremental period and 5th to 8th harvest years, could be considered as yield stabilizing period because of less yield increment and stable production from the palms(124.76 to 181 kg palm-1). Cumulative bunch production was higher in the cross NRCOP- 4 (96.18) with an yield of 159.3 t ha-1 in ten harvest years. Commercial plantations should be planted with high quality seedlings having more productivity. Field performance of dura x pisifera crosses have to be evaluated regularly in comparative trials for notable yield improvement.